Serum IL-17A Protein as a Potential Diagnostic and Prognostic Biomarker in Iraqi Colorectal Cancer Patients - Albujassim, Ameer S.; Khadhim, Manal Mohammed (Medical Science Journal for Advance Research, 2025)
Background: Colorectal cancer (CRC) remains a primary global health concern and ranks as one of the leading causes of cancer-related deaths worldwide. In Iraq, the incidence of CRC has increased over recent years, particularly among adults over the age of 40. Inflammation is recognized as a key driver of CRC progression, with interleukin-17A (IL-17A) identified as a crucial pro-inflammatory cytokine involved in tumor growth, immune modulation, and metastasis. Goal of study: Our study aimed to evaluate the serum levels of IL-17A in Iraqi CRC patients and to assess its potential diagnostic and prognostic significance. Material and Methods: A case-control study involved 60 clinically diagnosed CRC patients and 60 healthy controls matched for age and sex. Serum samples were collected, separated by centrifugation, and stored at –40°C. IL-17A levels were measured using a sandwich ELISA kit. Results: Clinical data were recorded for correlation analysis, including tumor grade, stage, and patient demographics. Serum IL-17A levels were significantly elevated in CRC patients compared to healthy controls (p<0.001). Higher IL-17A concentrations were associated with advanced tumor stage and poor differentiation. ROC curve analysis indicated good diagnostic potential, with IL-17A as a promising non-invasive biomarker. Furthermore, elevated IL-17A levels were linked to poorer overall survival, suggesting prognostic relevance. Conclusion: Serum IL-17A levels may serve as a valuable diagnostic and prognostic biomarker in Iraqi colorectal cancer patients. Further large-scale studies are needed to validate its clinical utility in CRC detection and management.